ACITYA: Augmented reality class design integrated Indonesian culture as a media to improve spatial ability - Detalia Noriza Munahefi; Hesty Ummi Wulandari; Nailin Nafiah Azzahra; Endang Retno Winarti (Universitas Sarjanawiyata Tamansiswa, 2024)
One of the abilities to face the challenges of the Society 5.0 era is spatial ability. However, the spatial abilities of Indonesian students are still low. This research aims to develop augmented reality-based classroom learning media integrated with Indonesian culture that is feasible, practical, and improves students' spatial abilities. The method used is the R&D method at the define, design, develop, and disseminate stages. Data collection techniques used were interviews, questionnaires, and tests. The research results showed that the application developed obtained an average percentage of feasibility from experts of 96.77% with very feasible criteria and from practitioners of 90.43% with very practical criteria. The results of the limited trial also showed an average increase in student learning outcomes of 667%. The ACITYA application is very feasible, very practical, and improves students' spatial abilities. Therefore, the ACITYA application has been distributed widely for use by students and teachers to improve spatial abilities.